2017
DOI: 10.1016/j.jacc.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Transcaval Access and Closure for Transcatheter Aortic Valve Replacement

Abstract: Background Transcaval access may enable fully percutaneous transcatheter aortic valve replacement (TAVR) without the hazards and discomfort of transthoracic (transapical or transaortic) access. Objectives We performed a prospective, independently-adjudicated, multi-center, single-arm Investigational Device Exemption trial of transcaval access for TAVR in patients ineligible for femoral artery access and high or prohibitive risk of complications from transthoracic access. Methods 100 subjects underwent atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(129 citation statements)
references
References 28 publications
2
127
0
Order By: Relevance
“…This percutaneous approach can be used for thoracic aortic aneurysm repair in patients with severe peripheral arterial disease, highly unusual anatomy, or those with contraindications to arterial access due to calcification or narrowed effective lumen diameter of the iliac or femoral arteries. Because of the novelty of this technique, further investigation regarding the largerscale cost-effectiveness and safety is warranted; however, an early study has indicated a successful transcaval access and closure in 99 out of 100 attempts during TAVR procedures (28,33). The one complication in this study occurred when the guidewire failed to cross and the operator had to perform transfemoral artery TAVR, which was further complicated by iliac artery rupture.…”
Section: Transcaval Accessmentioning
confidence: 85%
“…This percutaneous approach can be used for thoracic aortic aneurysm repair in patients with severe peripheral arterial disease, highly unusual anatomy, or those with contraindications to arterial access due to calcification or narrowed effective lumen diameter of the iliac or femoral arteries. Because of the novelty of this technique, further investigation regarding the largerscale cost-effectiveness and safety is warranted; however, an early study has indicated a successful transcaval access and closure in 99 out of 100 attempts during TAVR procedures (28,33). The one complication in this study occurred when the guidewire failed to cross and the operator had to perform transfemoral artery TAVR, which was further complicated by iliac artery rupture.…”
Section: Transcaval Accessmentioning
confidence: 85%
“…In unoperated patients, sharp wire puncture was used to create a restrictive 7 mm transcatheter Potts shunt (small descending thoracic aorta to left PA communication) surrogate in a small number of adults with end-stage PA hypertension (26). We employed our new transcatheter electro-wire crossing technique currently being used to enable precise crossing from inferior vena cava to aorta for temporary access prior to tract device closure (14,15). …”
Section: Discussionmentioning
confidence: 99%
“…We trained in the electro-wire crossing technique with experienced operators during clinical transcaval access for transcatheter aortic valve replacement (15). We planned the procedure step by step using pre-procedure contrast-enhanced computed tomography (CT) (Figure 2) (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcaval access appears a safe and reliable alternative for these patients. 1 Pressurization of the retroperitoneal space and consecutive drainage of aortic blood via shunting into the vena cava constitutes the pathophysiological concept underlying the feasibility of this approach. 1,2 No cases of transcatheter valve delivery via transcaval access without placing any sheath across the retroperitoneal space have been reported so far.…”
mentioning
confidence: 99%